Infectious Disease Management: Lessons from Cuba. Issue 4 (1st August 2006) - Macdonald, Noni E; Halperin, Beth; Chaple, Enrique Beldarrain; Scott, Jeff; Kirk, John M
Abstract : Over the past decade in Canada, infectious disease outbreaks have repeatedly been in the public spotlight. The Escherichia coli outbreak in Walkerton, Ontario (1), the severe acute respiratory syndrome outbreak in Toronto, Ontario (2) and the Clostridium difficile hospital outbreak in Montreal, Quebec (3), have cost lives, grabbed headlines and stressed local health care systems. Each outbreak raised questions about our ability to prevent outbreaks, detect outbreaks early, and respond efficiently and effectively to infectious disease crises; these outbreaks also highlighted gaps in Canada's preparedness for managing major infectious disease problems when multiple jurisdictions are involved (4). Canada's poor track record of tuberculosis control in the north (5) raises the concern that this problem is not limited to crisis situations, but rather has deeper implications for the management of infectious diseases in Canada.